Strategies for maximizing power and strength gains in isoinertial resistance training: Implications for competitive athletes - Sakamoto, A.; Sinclair, P. J.; Naito, H. (The Journal of Physical Fitness and Sports Medicine, 2016)
Isoinertial resistance is imposed during natural human dynamics, where muscles contract at varying velocities and joint angles. In many sports, the ability to produce greater force at faster speed is essential for successful outcomes. Hence, power training under isoinertial resistance (e.g., body mass, weights or flywheel, etc.) provides event-specific adaptive stimuli. Conventional power training consists of a combination of strength-oriented (> 70% 1RM) and speed-oriented (< 30% 1RM, e.g., plyometrics) methods, with the aim of being able to overcome variable external loadings across a range of velocities. An alternative maximum power output training (Pmax training, 30-70% 1RM) has been found to elicit equivalent or greater effectiveness compared to the conventional methods. It is, however, difficult to precisely reproduce the prescribed intensities, given several concerns associated with 1RM testing and the variable accuracies of the repetition-intensity or velocity-intensity relationship. No matter what level of resistance is assigned to an exercise, it is far more important to exert as much effort (or fastest concentric speed) as possible per repetition, otherwise, the training effects are reduced. At light intensities, however, a large portion of the concentric phase is spent in deceleration for the subsequent phase transition, which may limit effort. Making projectile motions, therefore, are necessary. The utilization of stretch-shortening cycle effects, with increased power ability, may give a further training edge. Coaches and trainees should be aware that successful movements in power training are defined as greater acceleration, speed and displacement for every repetition, rather than simply neat form or smooth repetitiveness.